Relationship of functional mitral regurgitation to new-onset atrial fibrillation in acute myocardial infarction. Issue 9 (27th April 2010) - Bahouth, Fadel; Mutlak, Diab; Furman, Moran; Musallam, Anees; Hammerman, Haim; Lessick, Jonathan; Dabbah, Saleem; Reisner, Shimon; Agmon, Yoram; Aronson, Doron
Abstract : Background/objective: The role of factors that increase left atrial pressure or cause acute left atrial dilatation is frequently emphasised in the pathogenesis of atrial fibrillation (AF) in patients with acute myocardial infarction (AMI). This study was designed to test the hypothesis that functional mitral regurgitation (FMR) occurring after AMI may promote AF by producing left atrial volume overload. Setting: Intensive care unit of a tertiary care hospital. Patients and Methods: 1920 patients admitted with AMI were studied. Patients with known AF were excluded. FMR was classified using echocardiography into three groups: none; mild FMR and moderate or severe FMR. The relationship between FMR and AF occurring at any time during the hospital course was examined using multivariable logistic regression. Results: Mild FMR was present in 744 patients (38.8%) and moderate or severe FMR was present in 150 patients (7.8%). AF developed in 51 (5.0%), 83 (11.2%) and 28 (18.7%) patients with no FMR, mild FMR and moderate or severe FMR, respectively (p trend <0.001). In multivariable logistic regression, both mild (odds ratio (OR) 1.6; 95% CI 1.1 to 2.3, p=0.02) and moderate or severe FMR (OR 2.1; 95% CI 1.2 to 3.6, p=0.007) were independent predictors of AF. There was a significant interaction between the left ventricular ejection fraction and FMR (p=0.003) such that mild FMR was predictive of AF only in patients with a reduced (<45%) ejection fraction. Conclusions: There is a graded independent association between the severity of FMR and the new onset of AF in patients with AMI.